Comprehensive numerical prototyping of paper-based microfluidic devices using open-source tools - Gerlero, Gabriel Santiago (2024)
Paper-based microfluidics has emerged as a promising field with diverse applications ranging from medical diagnostics to environmental monitoring. Despite significant progress in research and development, the translation of paper-based prototypes into practical end-user devices remains limited. This limitation stems from challenges related to devices not being sufficiently portable and autonomous, which paper-based microfluidics is expected to overcome. Yet for this purpose, we note the lack of comprehensive numerical modeling tools capable of simulating the intricate physicochemical phenomena involved in order to optimize the development process; hence, in this study, we introduce porousMicroTransport, a novel simulation package integrated with the open-source platform OpenFOAM®, designed to address these challenges. porousMicroTransport offers efficient solvers for fluid flow and transport phenomena in microfluidic porous media, including capillarity models and (bio)chemical reactions. Moreover, under horizontal flow conditions, porousMicroTransport application field can be extended to any porous media. We demonstrate the software’s effectiveness in two example cases, showcasing its ability to accurately reproduce complex phenomena involved in paper-based devices. By virtue of being an easy-to-use and computationally efficient tool, porousMicroTransport facilitates the design and optimization of devices, potentially enabling more devices to meet the WHO’s REASSURED criteria for point-of-care testing. We anticipate that this tool will accelerate the development and deployment of robust and portable diagnostic devices, bridging the gap between research and practical applications.